Performance evaluation and labor development of human talent management area at EsSalud Huánuco - 2011 - Lévano-Loayza, Luz E. (2019)
The objective of this study was to determine the relationship between performance and the labor development of human talent management area at Essalud, Huánuco, 2011. Methods: it was done a correlational study with 35 workers who responded an interview and two scales: performance evaluation and labor development. The inferential analysis was through the correlation Rho of Sperman for p≤ 0.05, supported by PASW V18.0. Results: there were moderated and positive correlations between performance evaluation and labor development of human talent, in dimensions: initiative (r= 0.51 and p≤ 0.002), teamwork (r=0.50 and p≤ 0.002) identification with the institution (r= 0.46 and p≤ 0.005); work organization and amount of work (r= 0.42 and p≤ 0.011); cultural sensitivity and work quality (r= 0.41 and p≤ 0.014); reliability (r= 0.40 and p≤ 0.017) and responsibility (r= 0.36 and p≤ 0.034). These results showed when the performance evaluation has a favorable outcome, it is the same for labor development. Communication dimension and labor development were independent [Rho Sperman 0.26 (low) and p≤ 0.131]. Conclusions: there is a moderate and positive correlation between performance evaluation human talent development (Rho Spearman 0.49 and p≤ 0.003) and it is necessary to manage human resources for a better performance and successful labor development.